2019
DOI: 10.3390/su11113208
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening and Repair of Reinforced Concrete Columns by Jacketing: State-of-the-Art Review

Abstract: Sustainability necessitates the protection of infrastructure from any kind of deterioration over the life cycle of the asset. Deterioration in the capacity of reinforced concrete (RC) infrastructure (e.g., bridges, buildings, etc.) may result from localised damage sustained during extreme loading scenarios, such as earthquakes, hurricanes or tsunamis. In addition, factors such as the corrosion of rebars or ageing may also deteriorate or degrade the capacity of an RC column, thereby necessitating immediate stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 92 publications
(97 reference statements)
0
43
0
2
Order By: Relevance
“…Several works from literature are focused on the experimental study of deteriorated RC columns under earthquake loading and their strengthening adopting different techniques. 4,5 The basic idea is to repair and use again deteriorated RC elements due to aging and Discussion on this paper must be submitted within two months of the print publication. The discussion will then be published in print, along with the authors' closure, if any, approximately nine months after the print publication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works from literature are focused on the experimental study of deteriorated RC columns under earthquake loading and their strengthening adopting different techniques. 4,5 The basic idea is to repair and use again deteriorated RC elements due to aging and Discussion on this paper must be submitted within two months of the print publication. The discussion will then be published in print, along with the authors' closure, if any, approximately nine months after the print publication.…”
Section: Introductionmentioning
confidence: 99%
“…Several works from literature are focused on the experimental study of deteriorated RC columns under earthquake loading and their strengthening adopting different techniques 4,5 . The basic idea is to repair and use again deteriorated RC elements due to aging and earthquake actions, as an important way to achieve a sustainable use of resources.…”
Section: Introductionmentioning
confidence: 99%
“…Raza, et al, [14] provided state of the art review of several strengthening and repair techniques for RC columns, suggested by many researchers in the last two decades. The most commonly used repair techniques presented included: Reinforced concrete/mortar jacketing, steel jacketing, externally bonded fiber-reinforced polymer of carbon and glass types (CFRP/GFRP) jacketing, basalt fiber-reinforced polymer (BFRP), near-surface mounted (NSM), FRP sheets with steel jacketing, and high-performance materials with steel/FRP rebars or FRP wrapping.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [3] reported a method to enhance the shear strength of RC columns through strengthening by a sprayed FRP system such as chopped glass and carbon fibers with epoxy or vinyl ester resin. Wang et al [4] found that the ductility and energy-dissipation capacities of non-ductile RC columns could be improved by retrofitting with CFRP wraps at the ends of the columns. Zoppo et al [5] observed increases in the capacity and ductility of columns reinforced with externally bonded FRP and an increase in the shear capacity with the application of discontinuous CFRP strips.…”
Section: Introductionmentioning
confidence: 99%